Performance of Ultrasound-Guided Core Biopsy Driven by FDG-avid Supraclavicular Lymph Nodes in Patients With Suspected Lung Cancer - Wang, Tongtong; Liu, Junbao; Lv, Ningning; Xuan, Shi; Bai, Lin; Ji, Bin; Gao, Shi (Frontiers in Medicine, 2022)
Objectives: Ultrasound-guided core biopsy (UGCB) for supraclavicular lymph nodes (SLNs) represents an attractive procedure to obtain tissues for lung cancer confirmation. The aim of the present study is to evaluate the performance of UGCB driven by FDG-avid SLNs, as performed by nuclear medicine radiologists, in patients with suspected lung cancer. Methods: Institutional database in our hospital was searched for eligible patients between September 2019 and March 2021. A 3-12 MHz linear probe was used to guide the biopsy process and to ensure that the needle tip was being directed at the metabolically active area that had been indicated by side-by-side PET/CT images. Diagnostic yield, malignancy rate, molecular testing results, and complications were reviewed. Results: Among the 54 patients included in this study, definite pathological diagnosis from UGCB specimens was achieved in 53 patients, reaching a diagnostic yield of 98.1% (53/54) and a malignancy rate of 96.2% (51/53). Among the 50 patients confirmed as lung cancer, thirty-eight were spared from further invasive procedures which had been planned. Molecular analyses were adequately performed on all the 38 specimens obtained from non-small cell lung cancer (NSCLS). The positive rate was 36.8% (14/38) for epidermal growth receptor (EGFR) mutation and 31.6% (12/38) for anaplastic lymphoma kinase (ALK) translocation. 28.9% (11/38) of the patients had a tumor proportion score (TPS) ≥ 50% for PD-L1 expression. No complication was observed. Conclusions: Nuclear medicine radiologists-performed UGCB driven by FDG-avid SLNs in suspected lung cancer patients could produce a high performance in terms of diagnostic yield, malignancy rate, and molecular analysis.